Proposta de um modelo conceitual para um sistema de planejamento de viagens utilizando STPP - Lira, Fabiano do Nascimento (2009)
The number of passengers transported by transit systems (TS) in Brazilian cities had their greatest value in the mid 90s. Thereafter, there was a large decrease, with a modest recovery in the last five years. Among the factors that attempt to explain this fall is the quality of the public systems considered well below that desired by the population to carry out their trips. The systems planning trips (TPS) using STPP is a improvement that has been studied recently, especially with the advent of technologies for capturing and transmission of digital data. There are several models of SPV in various cities around the world, considering factors such as local culture in relation to transport; however, there are few Brazilian cities that have a similar system. This research is devoted to propose a model of conceptual model of a TPS, in order to guide users in the use of TS and let you aware the characteristics of such use.